Railway system accessibility evaluation for wheelchair users: case study in the Czech Republic - Matuška, Jaroslav (Transport, 2017)
This paper deals with accessibility of rail transportation as a system. Presented methods bring ways of rail infrastructure and train accessibility evaluation. Applied two-stage model enables evaluation of departure halls accessibility. The level of train accessibility is defined by coefficients of time and direction non-uniformity. While opportunities for barrier-free travelling are relatively balanced in monitored regions, coefficients show a time imbalance in the results. Opportunity to travel barrier-free (according to the non-uniformity coefficients) shows that there are fluctuations at weekends and on weekdays. These are not of crucial importance. However, the train services are barrier-free particularly for travelling on long distances, whilst suburban and regional ones are still mostly inaccessible for wheelchairs, which is not very favourable. Since 2010 the accessibility level has improved in this area in the Czech Republic. Comparison with neighbouring countries showed strong and weak points of guaranteed barrier-free services in each country.First published online: 28 Aug 2014